Moonwalking with Einstein : the art and science of remembering everything - Foer, Joshua (New York : Penguin Press, 2011)
Having achieved the seemingly unachievable-- becoming a U.S. Memory Champion-- Foer shows how anyone with enough training and determination can achieve mastery of their memory.
The smartest man is hard to find -- The man who remembered too much -- The expert expert -- The most forgetful man in the world -- The memory palace -- How to memorize a poem -- The end of remembering -- The ok plateau -- The talented tenth -- The little rain man in all of us -- The US memory championships.
Includes bibliographical references (p. [289]-297) and index.
Keywords: Mnemonics; Memory